1/4+12/16
1+ 1/4+1/8+1/16
2-1/8-1/12-1/16
4/99*18/5:12/11+3/5
(1-3/4)*(1+1/3):(1-1/3)
\(1+\dfrac{1}{4}+\dfrac{1}{8}+\dfrac{1}{16}\)
\(=\dfrac{5}{4}+\dfrac{1}{8}+\dfrac{1}{16}\)
\(=\dfrac{11}{8}+\dfrac{1}{16}\)
\(=\dfrac{23}{16}\)
______
\(2-\dfrac{1}{8}-\dfrac{1}{12}-\dfrac{1}{16}\)
\(=\dfrac{15}{8}-\dfrac{1}{12}-\dfrac{1}{16}\)
\(=\dfrac{43}{24}-\dfrac{1}{16}\)
\(=\dfrac{83}{48}\)
_________
\(\dfrac{4}{99}\times\dfrac{18}{5}:\dfrac{12}{11}+\dfrac{3}{5}\)
\(=\dfrac{8}{55}:\dfrac{12}{11}+\dfrac{3}{5}\)
\(=\dfrac{8}{55}\times\dfrac{11}{12}+\dfrac{3}{5}\)
\(=\dfrac{2}{15}+\dfrac{3}{5}\)
\(=\dfrac{11}{15}\)
__________
\(\left(1-\dfrac{3}{4}\right)\times\left(1+\dfrac{1}{3}\right)\times\left(1-\dfrac{1}{3}\right)\)
\(=\dfrac{1}{4}\times\dfrac{4}{3}\times\dfrac{2}{3}\)
\(=\dfrac{4\times2}{4\times3\times3}\)
\(=\dfrac{2}{3\times3}\)
\(=\dfrac{2}{9}\)
2 tính : a) 1+1/4+1/8+1/16 =
=
b) 2-1/8-1/12-1/16 =
=
c) 4/99 x 18/5 : 12/11 + 3/5 =
=
d) ( 1-3/4 ) x ( 1+ 1/3 ) : ( 1- 1/3 ) =
=
a) 1 + 1/4 + 1/8 + 1/16
= 16/16 + 4/16 + 2/16 + 1/16
= 23/16
b) 2 - 1/8 - 1/12 - 1/16
= 96/48 - 6/46 - 4/48 - 3/48
= 83/48
c) 4/99 × 18/5 : 12/11 + 3/5
= 8/55 : 12/11 + 3/5
= 2/15 + 3/5
= 2/15 + 9/15
= 11/15
d) (1 - 3/4) × (1 + 1/3) : (1 - 1/3)
= 1/4 × 4/3 : 2/3
= 1/3 : 2/3
= 2
1 + 1/4 + 1/8 + 1/16
= 16 + 4 + 2 + 1 / 16
=23/16
2-1/8-1/12-1/16
= 96 - 6 - 4 - 3 / 48
= 83 / 48
4/99 x 18/5 : 12 /11 + 3/5
= 4/99 x 18/5 x 11/12 + 3/5
= 2/15 + 3/5
= 11/15
(1 - 3/4) x (1+1/3) : (1-1/3)
= 1/4 x 4/3 : 2/3
= 1/4 x 4/3 x 3/2
= 1/2
A= \(A=1*2*3+2*4*6+4*8*12+8*16*24 \over 2*3*4+4*6*8+8*12*16+16*24*32\)
mình xin nhầm đề là: A = \(1*2*3+2*4*6+4*8*12+8*16*24 \over2*3*4+4*6*8+8*12*16+16*24*32\)
a, 21/11-9/19-3/19-12/38-24/22
b,2/3+3/4+4/5+12/9+28/16+48/15
c,4/5-1/2-1/4-1/8-1/16/1/36
a, 21/11-9/19-3/13-12/38-24/22 =21/11-(9/19-3/13)-12/38-24/22 =207/143-12/38-24/22 =3075/2717-24/22 =111/2717 b,2/3+3/4+4/5+12/9+28/16+48/15 =17/12+4/5+12/9+28/16+48/15 =133/60+12/9+28/16+48/15 =71/20+28/16+48/15 =53/10+48/15 =17/2 c, 4/5-1/2-1/4-1/8-1/16-1/36 =3/10-1/4-1/8-1/36 =1/20-1/8-1/16-1/36 =-3/40-1/16-1/36 =-11/60-1/36=-119/720
1*2*4+2*4*8+4*8*16+8*16*32/1*3*4+2*6*8+4*12*16+8*24*32
Tính
1*2*4+2*4*8+4*8*16+8*16*32/1*3*4+2*6*8+4*12*16+8*24*32 = 56744
1*2*4+2*4*8+4*8*16+8*16*32/1*3*4+2*6*8+4*12*16+8*24*32 = 56744
#nhớ tk
tính nhanh hộ mình 2 câu này với :
1*2+2*4+3*6+4*8+5*10 / 3*4+6*8+9*12+12*16+15*20
2*4+2*4*8+4*8*16+8*16*32 / 3*4+2*6*8+4*12*168*24*32
a)
\(\frac{1.2+2.4+3.6+4.8+5.10}{3.4+6.8+9.12+12.16+15.20}\)
\(\frac{2.3\left(1.2\right)+2.3\left(2.4\right)+2.3\left(3.6\right)+2.3\left(4.8\right)+2.3\left(5.10\right)}{3.4\left(3.4+6.8+9.12+12.16+15.20\right)}\)
\(=\frac{\left(3.4+6.8+9.12+12.16+15.20\right)}{2.3\left(3.4+6.8+9.12+12.16+15.20\right)}=\frac{1}{2.3}=\frac{1}{6}\)
4/5 : ( 4/5 . -5/4) : ( 16/25 - 1/5 )
11/12 : ( 7/9 + -1/3 ) - ( 2/3 - 5/15 )
-2/5 . ( 9/8 + 16/32 -3/4 ) - 9/10
( 4/3 + 8/3 ) . ( 7/4 - 6/4 ) : ( 6/5 + 12/5 + 1/5 )
cách giải bài này như nào: 5/20+1/4+6/24+8/32=bao nhiêu
\(\dfrac{4}{5}\) : (\(\dfrac{4}{5}\) .- \(\dfrac{5}{4}\)) : (\(\dfrac{16}{25}\) - \(\dfrac{1}{5}\))
= \(\dfrac{4}{5}\) : (-1) : (\(\dfrac{16}{25}\) - \(\dfrac{5}{25}\))
= -\(\dfrac{4}{5}\) : \(\dfrac{11}{25}\)
= - \(\dfrac{4}{5}\) x \(\dfrac{25}{11}\)
= - \(\dfrac{20}{11}\)
\(\dfrac{11}{12}\) : (\(\dfrac{7}{9}\) + \(\dfrac{-1}{3}\)) - (\(\dfrac{2}{3}\) - \(\dfrac{5}{15}\))
= \(\dfrac{11}{12}\) : (\(\dfrac{7}{9}\) - \(\dfrac{3}{9}\)) - (\(\dfrac{2}{3}\) - \(\dfrac{1}{3}\))
= \(\dfrac{11}{12}\) : \(\dfrac{4}{9}\) - \(\dfrac{1}{3}\)
= \(\dfrac{11}{12}\) x \(\dfrac{9}{4}\) - \(\dfrac{1}{3}\)
= \(\dfrac{99}{48}\) - \(\dfrac{1}{3}\)
= \(\dfrac{99}{48}\) - \(\dfrac{16}{48}\)
= \(\dfrac{83}{48}\)
4/5 : ( 4/5 . -5/4) : ( 16/25 - 1/5 )
11/12 : ( 7/9 + -1/3 ) - ( 2/3 - 5/15 )
-2/5 . ( 9/8 + 16/32 -3/4 ) - 9/10
( 4/3 + 8/3 ) . ( 7/4 - 6/4 ) : ( 6/5 + 12/5 + 1/5 )
\(\dfrac{4}{5}\): (\(\dfrac{4}{5}\).-\(\dfrac{5}{4}\)) : (\(\dfrac{16}{25}\) - \(\dfrac{1}{5}\))
=\(\dfrac{4}{5}\) x - 1: (\(\dfrac{16}{25}\) - \(\dfrac{5}{25}\))
= - \(\dfrac{4}{5}\) : \(\dfrac{11}{25}\)
= - \(\dfrac{4}{5}\) x \(\dfrac{25}{11}\)
= - \(\dfrac{20}{11}\)
\(\dfrac{11}{12}\): (\(\dfrac{7}{9}\) + - \(\dfrac{1}{3}\)) - (\(\dfrac{2}{3}\) - \(\dfrac{5}{15}\))
= \(\dfrac{11}{12}\) : (\(\dfrac{7}{9}\) - \(\dfrac{3}{9}\)) - (\(\dfrac{2}{3}\) - \(\dfrac{1}{3}\))
= \(\dfrac{11}{12}\) : \(\dfrac{4}{9}\) - \(\dfrac{1}{3}\)
= \(\dfrac{11}{12}\) x \(\dfrac{9}{4}\) - \(\dfrac{1}{3}\)
= \(\dfrac{99}{48}\) - \(\dfrac{16}{48}\)
= \(\dfrac{83}{48}\)
- \(\dfrac{2}{5}\).(\(\dfrac{9}{8}\) + \(\dfrac{16}{32}\) - \(\dfrac{3}{4}\)) - \(\dfrac{9}{10}\)
= - \(\dfrac{2}{5}\).(\(\dfrac{9}{8}\) + \(\dfrac{4}{8}\) - \(\dfrac{6}{8}\)) - \(\dfrac{9}{10}\)
= - \(\dfrac{2}{5}\).(\(\dfrac{13}{8}\) - \(\dfrac{6}{8}\)) - \(\dfrac{9}{10}\)
= - \(\dfrac{2}{5}\).\(\dfrac{7}{8}\) - \(\dfrac{9}{10}\)
= - \(\dfrac{7}{20}\) - \(\dfrac{18}{20}\)
= - \(\dfrac{5}{4}\)
( 1/2 +1 ) .( 1/3 +1 ) .(1/4+1) ........(1/99+1)
9/13 + 9/16 - 9/23
12/13 +12/16 -12/23
tính
Bài 13: Dấu <, =, >
10 … 10 + 3
11 + 2…. 2 + 11
9 … 10 + 9
10 … 10 + 0
17 – 4 … 14 - 3
18 – 4 … 12
15 … 15 – 1
17 + 1… 17 + 2
12+ 5 … 16
16 … 19 - 3
15 – 4 … 10 + 1
19 – 3 … 11
10 < 10 + 3
11 + 2=2 + 11
9 < 10 + 9
10 = 10 + 0
17 – 4 > 14 - 3
18 – 4 >12
15 > 15 – 1
17 + 1<17 + 2
12+ 5 > 16
16 =19 - 3
15 – 4 =10 + 1
19 – 3 >11